Non-Directed β- or γ-C(sp3)–H Functionalization of Saturated Nitrogen-Containing Heterocycles - Ohno, Shohei; Miyoshi, Makoto; Murai, Kenichi; Arisawa, Mitsuhiro (Synthesis, 2021)
Reactions that take place via C–H functionalization are valuable tools in organic synthesis because they can be used for the synthesis of target compounds and for the late-stage functionalization of bioactive compounds. Among these, non-directed C(sp3)–H functionalization reactions of saturated nitrogen-containing heterocycles have been developed in recent years. However, most of these lead to functionalization at the α-position relative to the heteroatom, and reactions at the β- or γ-positions are limited since these bonds are stronger and less electron-rich. Hence, in this review, we will discuss non-directed β- or γ-C(sp3)–H functionalization reactions of saturated nitrogen-containing heterocycles, which are of recent interest to medicinal chemists. These methods are attractive in order to avoid the pre-functionalization of substrates, and to reduce the number of synthetic steps and the formation of byproducts. Such non-directed β- and γ-C(sp3)–H functionalization reactions can be divided into enamine-intermediate-mediated processes and other reaction types described in this review. 1 Introduction2 Non-Directed β-C(sp3)–H Functionalization of Saturated Nitrogen-Containing Heterocycles via an Enamine Intermediate2.1 Non-Directed β-C(sp3)–H Functionalization of Saturated Nitrogen-Containing Heterocycles under Acidic, Basic or Thermal Conditions2.2 Non-Directed β-C(sp3)–H Functionalization of Saturated Nitrogen-Containing Heterocycles under Oxidative Conditions2.3 Non-Directed β-C(sp3)–H Functionalization of Saturated Nitrogen-Containing Heterocycles under Redox-Neutral Conditions3 Strategies for Non-Directed β- or γ-C(sp3)–H Functionalization of Saturated Heterocycles Excluding Examples Proceeding via an Enamine Intermediate 4 Summary
Keywords: directing-group-free; C(sp3)–H functionalization; nitrogen-containing heterocycles; enamine intermediate; borrowing hydrogen; late-stage functionalization